2011
DOI: 10.1248/cpb.59.529
|View full text |Cite
|
Sign up to set email alerts
|

Formulation Variation and in Vitro-in Vivo Correlation for a Rapidly Swellable Three-Layered Tablet of Tamsulosin HCl

Abstract: Regular ArticleA novel three-layered tablet technology consisting of an inner immediate release layer and two extended release barrier layers with swellable polymers has been suggested and investigated as once-a-day tablet formulations. 1) In that formulation, dissolution medium quickly permeates to the inner layer of water-soluble excipients, and the two barrier layers swell to surround the inner layer rapidly, controlling drug release from the inner layer. After oral administration, the tablet might become f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 22 publications
(30 reference statements)
0
0
0
1
Order By: Relevance
“…The Tmax of a commercial tamsulosin-loaded immediate-release formulation in beagle dogs has been reported to be within 1 h [36]. In this study, both formulations showed an increased T max , indicating a sustained release pattern [37]. Moreover, no significant differences were observed in their pharmacokinetic parameters, including AUC, C max , and T max (45.988 ± 15.345 vs. 46.251 ± 14.245 h•ng/mL; 7.237 ± 2.324 vs. 7.625 ± 2.634 ng/mL; 2.833 ± 0.718 vs. 2.917 ± 0.515 h, respectively).…”
Section: Pharmacokineticsmentioning
confidence: 56%
“…The Tmax of a commercial tamsulosin-loaded immediate-release formulation in beagle dogs has been reported to be within 1 h [36]. In this study, both formulations showed an increased T max , indicating a sustained release pattern [37]. Moreover, no significant differences were observed in their pharmacokinetic parameters, including AUC, C max , and T max (45.988 ± 15.345 vs. 46.251 ± 14.245 h•ng/mL; 7.237 ± 2.324 vs. 7.625 ± 2.634 ng/mL; 2.833 ± 0.718 vs. 2.917 ± 0.515 h, respectively).…”
Section: Pharmacokineticsmentioning
confidence: 56%
“…Da bi se uspostavila korelacija nivoa A koja bi bila prihvaćena od strane regulatornih organa u svrhu biowaiver-a, ovaj model korelacije mora biti validiran i razvijen na najmanje 3 formulacije različitih brzina rastvaranja [111]. U literaturi se mogu naći i primeri uspostavljanja IVIVK nivoa A za samo jednu formulaciju [149][150][151]. Iako ovakvi modeli nemaju regulatorni značaj, oni mogu značajno doprineti razvoju relevantnog testa brzine rastvaranja i mogu dodatno biti prošireni u pravu IVIVK nivoa A. Kako profil in vivo brzine rastvaranja nije moguće direktno meriti, za njegovu procenu koriste se različiti matematički modeli izračunavanja.…”
Section: In Vitro-in Vivo Korelacija Nivoa Aunclassified